Sports and energy drink consumption, oral health problems and performance impact among elite athletes - Khan, K.; Qadir, A.; Trakman, G.; Aziz, T.; Khattak, M. I.; Nabi, G.; Alharbi, M.; Alshammari, A.; Shahzad, M. (Nutrients, 2022)
Frequent consumption of sports and energy drinks among athletes is of concern due to its detrimental impact on oral health. The present study aimed to assess sports and energy drink consumption, oral health status and impacts on daily activities and sports performance among elite athletes from Pakistan. Data regarding socio-demographic characteristics, sports and energy drink consumption, oral health and hygiene practices, self-reported oral health and psychosocial and performance impact was assessed using a self-administered, structured questionnaire followed by clinical oral examination by a single, experienced dentist. A total of 104 athletes, a majority of whom were male (80.8%), participated in the study. Around two third of the participants reported consumption of sports and energy drinks, energy gels or bars at least once a week, the commonest being Sting. Despite good oral hygiene practices, the athletes generally had poor oral health with high prevalence of dental caries (63.5%), gingivitis (46.1%), irreversible periodontitis (26.9%) and erosive tooth wear (21.2%). More than a quarter (28.8%) of the athletes rated their oral health as fair—very poor. Four in five athletes (80%) also experienced at least one oral problem with negative impacts on daily activities (64.4%) and participation training and sports performance (36.5%). Regression analyses revealed a significant association between periodontal disease and impact on both daily activities and sports performance. To our knowledge, this is the first study reporting that high-prevalence sports and energy drink consumption and oral problems among elite athletes from Pakistan has a negative impact on daily activities and sports performance. These findings may have important implications for oral health education programs, and the need to create awareness among the athletes regarding the use of sports and energy drinks, as well as regular oral health screening of athletes to minimize the impact on performance.